Analisis Peran Regulasi Emosi Mahasiswa terhadap Kebijakan School From Home Di Masa Pandemi Covid 19 - Januar Eko Aryansah; Syska Purnama Sari (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
The school from home policy is formulated by the government in an emergency. The policy issued aims to resolve the spread of Covid 19, a policy issued without considering the response of policy implementers or from parties affected by the policy, in this policy the parties affected as policy targets are stakeholders in the field of education, They are lecturers, teachers, students and students, including parents. However, not students who implement the school from home policy complain about the learning process they receive, because there are so many problems that arise in the process of implementing the policy. So that what students or students need most in a situation like this is emotional regulation skills. Emotional regulation is needed so that students can remain calm even though they have difficulties in life. The purpose of this study was to analyze the role of student emotion regulation on government policy school from home during the Covid 19 pandemic. The method used is the literature method. The result of the research is that emotional regulation is very important for students to be able to face problems in the learning process that is carried out from home. The important role of emotional regulation in the school from home policy is (1) Emotional regulation can reduce student stress levels because they face learning problems from home and (2) emotional regulation can build student resilience so that students are able to rise and survive in a covid 19 pandemic situation. Keywords : Emotion Regulation, Public Policy, School From Home, Covid 19